A Word of Caution for Gossypiboma - YILDIZELİ, BEDRETTİN (GEORG THIEME VERLAG KG, 2022)
Gossypiboma, a retained nonabsorbable surgical sponge, is a major safety issue despite being infrequent, causing serious malpractice debates. In addition to this, it may mimic a range different disease within the thorax and even have unpleasant clinical presentations even after years. In this article, we report four gossypiboma cases with nonspecific clinical presentations to emphasize the importance of keeping this diagnosis in mind with all patients who have had a previous operation.
Keywords: gossypiboma; foreign body; surgery; complications; THORACIC TEXTILOMAS